Socialization Of Tourism Awareness As An Effort To Increase The Role Of The Community In The Development Of Tourist Destinations In Batam City - Moh. Thandzir; Dailami; Tito Pratama; Haufi Sukmamedian; Wahyudi Ilham; Natal Olotua Sipayung; Rezki Alhamdi; Abd Rahmad Yusuf (JURNAL KEKER WISATA, 2026)
The Community Service Activity (PKM) with the title "Socialization of Tourism Awareness as an Effort to Increase the Role of the Community" aims to increase public understanding, awareness, and participation in supporting tourism development in their area. This activity is motivated by the importance of the role of the community as the main actor in creating a safe, comfortable, clean, and competitive tourism environment. The implementation of the activity is carried out through socialization, counseling, and interactive discussions involving local communities, community leaders, and other stakeholders. The material presented includes the concept of tourism awareness, the principle of Sapta Pesona, and the importance of friendly service and environmental preservation in supporting the attractiveness of tourist destinations. The results of the activities show an increase in public understanding of the importance of tourism awareness and their role in maintaining the image of the destination. The community has also begun to show an attitude of being more concerned about the cleanliness, safety, and comfort of the tourist environment, and is encouraged to actively participate in tourism activities. Thus, this PKM activity is expected to build community collective awareness so that it is able to play an active role in the development of sustainable tourism, as well as have a positive impact on improving the economy and the welfare of local communities.